Role of Risk Management in Independent Commissioners and Audit Committees on Financial Performance - Iskandar Itan; Khelen Khelen (Global Financial Accounting Journal, 2022)
Purpose - Financial performance of a company is an important thing to consider due to its direct correlation with the company’s survivability. It is important to understand what affects a company's financial performance. This research aimed to determine the influence of the independent commissioner and audit committee variables on financial performance as moderated by risk management. Research Method - This study used 22 companies of LQ-45 that listed in the Indonesia Stock Exchange from 2017 to 2021 using a purposive sampling method. Model used in this research was analyzed using multiple linear regression. Findings – The results indicate that independent commissioners have no significant effect on financial performance, while audit committee has a positive significant effect on the financial performance. Independent commissioners and audit committee simultaneously have a positive and significant effect on the financial. While risk management was not found to moderate the effect of independent commissioners on financial performance, though it may strengthen the relationship between audit committee and financial performance. Implication – The presence of independent commissioners and audit committee in a company is important because independent commissioners act as an external party entitled to monitor the actions taken by the company, while audit committee affects reliable and accountable financial statements. Every company certainly has risks that must be taken and make adjustments according to the level of risk. Furthermore, having risk management in the companies enable the audit committees to assess the risk more accurate.